Efficacy of oral oxytetracycline therapy against Aeromonas caviae infection in Nile tilapia Oreochromis niloticus (L.) juveniles - Anwesha Roy; Thangapalam Jawahar Abraham; Jasmine Singha; Roy Beryl Julinta; Satyanarayana Boda (Journal of Fisheries, 2021)
The present study evaluated the effects of Aeromonas caviae infection and oral oxytetracycline (OTC) therapy based on the histopathological alterations, serum creatinine, and antibiotic resistance in the gut-bacteria of Oreochromis niloticus. Ten days of OTC therapy at 2 g kg feed–1 at 3% body weight reduced the mortalities to 30% compared to 50% in the abrasion-immersion (AI) challenged and untreated group. The feed intake was reduced in challenged fish, which consumed about 42 mg OTC against the recommended minimum therapeutic dose of 55 mg kg biomass–1 day–1. The OTC-resistant gut bacteria increased by 5.84 folds in 10 days of OTC feeding. The fish kidney exhibited glomerulopathy, nephropathy including nephritis, and lost its structural integrity within 5 days post-injection. An improved structural organization of glomerulus and renal tubules was noted with OTC therapy. Despite the improved kidney functions, as confirmed by the serum creatinine levels, the fish could not recuperate fully on day 21 post-OTC therapy. The initial high mortalities in A. caviae challenged fish suggested that the dose and feed ration used in this study was only partially effective. The findings of the present study may be useful while planning the mitigation strategies for disease management.